Clays Are Not Created Equal: How Clay Mineral Type Affects Soil Parameterization. Issue 20 (20th October 2021) - Lehmann, P.; Leshchinsky, B.; Gupta, S.; Mirus, B. B.; Bickel, S.; Lu, N.; Or, D.
Abstract: Clay minerals dominate the soil colloidal fraction and its specific surface area. Differences among clay mineral types significantly influence their effects on soil hydrological and mechanical behavior. Presently, the soil clay content is used to parameterize soil hydraulic and mechanical properties (SHMP) for land surface models while disregarding the type of clay mineral. This undifferentiated use of clay leads to inconsistent parameterization, particularly between tropical and temperate soils, as shown herein. We capitalize on recent global maps of clay minerals that exhibit strong climatic and spatial segregation of active and inactive clays to consider spatially resolved clay mineral types in SHMP estimation. Clay mineral‐informed pedotransfer functions and machine learning algorithms trained with datasets including different clay types and soil structure formation processes improve SHMP representation regionally with broad implications for hydrological and geomechanical Earth surface processes. Plain Language Summary: Understanding and predicting Earth's surface water and energy movement rely on accurate representation of soil properties, which are often estimated using simple‐to‐measure information such as soil particle sizes (soil texture) and other attributes, such as vegetation. Soil clay content is an important trait that affects the rate by which rainwater infiltrates the soil and potentially the stability of soil on steep hillslopes. Most models make no distinction between clay minerals despite large differences in clay mineral and soil properties between tropical and temperate regions. New global maps of clay minerals show strong climatic and spatial segregation of clay minerals that allow better estimates of fundamental soil properties. We developed models that use these clay mineral maps for estimating hydrological and mechanical properties for most soil types. These new equations will help to improve global predictions of water availability, erosion, and natural hazards. Key Points: Variations in clay mineral type significantly affect soil hydro‐mechanical properties for soils with similar clay fractions Recent global maps of clay mineral type permit spatially resolved and physically based corrections of pedotransfer functions The new clay mineral‐informed soil properties are in agreement with measurements and resolve biases of undifferentiated use of clay faction